Religion and Religious Doubt: Predictors of Psychological Distress in Emerging Adults - John W Lace; Paul J Handal (Universitas Ahmad Dahlan, 2017)
Â AbstractÂ The present study examined the predictive effect of religious dimensions and religious doubt on psychological distress in emerging adult males and females. Participants included 637 (440 females) individuals from a religiously affiliated, Midwestern university. Data were collected online, and 66% of participants received extra credit for participating. Respondents completed the Personal Religious Inventory to assess their self-report of dimensions of religion; a single-item measure of religious doubt to understand the degree of certainty or doubt about their religious beliefs; and the Langner Symptom Survey to assess the severity of reported psychological distress. Results indicated that dimensions of religion and religious doubt significantly predicted psychological distress only in emerging adult females. Religion and religious doubt were not predictive of psychological distress for emerging adult males. The present study suggests the relationships among religious dimensions, religious doubt, and psychological distress may be unique for men and women and discusses possible reasons.Â Keywords: religious doubt, psychological distress, emerging adults, sex differences